Correlation of Meaning of The Garebeg Mulud Traditional Ceremony Series: Sekaten, Gamelan and Tourism - Hakim, Lutfi Maulana; Kusumastiti, Weka (Program Studi Antropologi Sosial Pascasarjana Universitas Negeri Medan, 2024)
The Garebeg Mulud celebration is one of a series of traditional ceremonies included in the Yogyakarta Palace Hajad Dalem event which is held annually. Garebeg Mulud itself is one of the celebrations of the Hajad Dalem ceremony whose series of events are quite long because, in the Muludan ceremony, there is a Sekaten celebration whose series of events lasts for 7 days. now many people interpret garebeg mulud as the same as the sekaten night market. at the same time, sekaten is only one of the series of events at gerbeg mulud which is full of meaning. this research aims to explain more about the series of Garebeg Mulud ceremonies and the meaning and philosophy embedded in each series of events from Miyos Gongso to Bedhol Songsong. This series of Hajad Dalem events is not only a celebration but ultimately also a tourist attraction for the community. Public interest in attending the Hajad Dalem ceremony is very high. This positive reaction creates a sense of love, and care and continues to preserve this noble culture